Prioritization of zoonoses for multisectoral, One Health collaboration in Somalia, 2023 - Osman, A.Y.; Mohamed, H.; Mumin, F.I.; Mahrous, H.; Saidouni, A.; Elm, S.A.; Adawe, A.K.; Mo'allim, A.A.; Lubogo, M.; Malik, S.M.M.R.; Mwatondo, A.; Raji, T.; et al. (Elsevier, 2023)
Background The population of Somalia is vulnerable to zoonoses due to a high reliance on animal husbandry. This disease risk is exacerbated by relatively low income (poverty) and weak state capacity for health service delivery in the country as well as climate extremes and geopolitical instability in the region. To address this threat to public health efficiently and effectively, it is essential that all sectors have a common understanding of the priority zoonotic diseases of greatest concern to the country.